A response from Francis Watson - Watson, Francis (Scottish journal of theology, 2006)
It is an honour and a pleasure to respond to the comments of J. Louis Martyn and Troels Engberg-Pedersen. Both of them have read my book with care, and have presented many of its central emphases with clarity and insight. The questions they raise are pertinent ones – as one would expect from the authors of two of the most interesting and innovative works of Pauline scholarship to have been published in recent years. I refer to Martyn's commentary on Galatians and Engberg-Pedersen's Paul and the Stoics – both, in their different ways, the kind of ground-breaking work that keeps the field of Pauline studies from succumbing entirely to an endless rehearsal of already familiar positions. I also note in passing that my two reviewers probably differ more sharply from each other than either of them does from me. It is not easy to harmonise Martyn's apocalyptic Paul with Engberg-Pedersen's Stoic one, and the difference tends to focus on issues of divine agency which recur in their responses to my own work.